Penerapan Prototipe Mesin Pengisi Gelas Semi Otomatis untuk Efisiensi Air Minum Kemasan - Zainal Abidin Achmad; R. Ayu Firdausi Novira Rachman; Pungky Febi Arifianto; Zatin Niqotaini; Sjafiatul Mardliyah (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Saringembat Village, Singgahan District, Tuban Regency, faces the challenge of high-calcium groundwater quality, which contributes to high stunting rates. To address this issue, the UPN "Veteran" East Java community service team developed a prototype for a semi-automatic, energy-efficient, and easy-to-operate plastic cup filling machine. The project, conducted in collaboration with the Mekar Sari Saringembat Village-Owned Enterprise (BUMDes), involved designing the machine, creating a logo and brand for the drinking water product, training in machine operation, and developing branding and marketing strategies. The results of the project include: (1) the availability of a low-power (180–250 Watt) cup filling machine prototype; (2) the registration of the drinking water logo and trademark design; (3) increased capacity of BUMDes human resources in operations, maintenance, and marketing; and (4) the establishment of a new village-based bottled water business unit. This program supports SDGs 3 (Good Health and Well-being) and SDG 8 (Decent Work and Economic Growth). Going forward, this innovation can be replicated in other areas facing similar challenges.